Customer discrimination in the fast food market? Experimental evidence from a Swedish university campus - Ali M. Ahmed; Mats Hammarstedt (Research Institute of Industrial Economics (IFN), 2018)
This paper studies customer discrimination against fictive male and female food truck owners with Arabic names on a Swedish University campus using a web-based experiment.Students at a Swedish university campus were asked to participate in a market survey and state if they think it is a good idea to have a food truck establishment on the campus. Further, they were also asked about their own beliefs, and their beliefs about others' willingness to pay for a baguette and a kebab sold by the food truck on the campus. Four names - one male Swede, one female Swede, one male Arab, and one female Arab - were randomly assigned to the food truck. We found no evidence of customer discrimination against food truck owners with Arabic names. In fact, the respondents were slightly more positive to a food truck establishment run by an Arabic male than by a Swedish male. We conclude that our results are representative in an environment with relatively young and highly educated customers and that customer discrimination may vary across different markets. More research in this area is needed.
Keywords: J15; J16; J79; 330; Customer discrimination; Self-employment; Immigrants; Sweden